Digital Tourism Training for Tourism Awareness Groups in Galanti Village, Buton Regency - Sadat, Anwar; Lawelai, Herman; Hastuti, Hastuti; Tasmin, La Ode; Nurfaiza, Nurfaiza; Restiani, Sitti Ainun (Edumedia Solution, 2023)
The purpose of this community service is to provide a solution to solving this problem, namely to digitize the marketing of Galanti Village tourist objects so that it is expected to be able to provide broad information about tourism in Galanti Village, which has the potential to increase the number of visitors so as to be able to revive the community's economy. The solution offered by the service team to overcome this problem is to provide digital marketing training for village officials, young people, and tourism awareness groups, as well as community groups managing Galanti Village tourism. Digital marketing is an activity to disseminate information with the support of internet technology to maximize marketing strategies; however, digital marketing does not only focus on technology but how individuals or groups can use this technology to be used as promotional media. Thus, this service provides digital marketing training that aims to increase the knowledge and skills of village officials and tourism awareness groups, which are also community groups managing tourism, in promoting tourism potential and home industries in Galanti Village by utilizing the technology they have, namely smartphones.